Concise total synthesis of (+)-lanceolactone a: revision of absolute stereochemistry - Borade, Balasaheb R.; Kontham, Ravindar (Journal of Organic Chemistry, 2022)
A chiral-pool protecting-group-free five-step total synthesis of tetranorsesquiterpenoide (+)-lanceolactone A and all of its four stereoisomers using (S)-(+)-, and (R)-(-)-linalool (coriandrol) as building blocks is disclosed. The key steps involved in this synthetic route are regioselective ozonolysis, Au(I)-catalyzed cycloisomerization-induced construction of furan from alleneone, and dye-sensitized photo-oxidation (through O-1(2) ; singlet oxygen) of hydroxyalkyl-tethered furan to access oxaspirolactone. After a thorough evaluation of electronic circular dichroism (ECD) and optical rotation data of all possible stereoisomers, the absolute configuration of natural lanceolactone A at the C4 and C7 positions has been assigned as (+)-(4S,7S), which is an enantiomer to the initially proposed structure (+)-(4R,7R). Further, these investigations led us to extend Feringa and Gawronski's CD correlation method to [5,5]- and [6,5]-oxaspirolactones.

Concise and collective total syntheses of 2,4-disubstituted furan-derived natural products from hydroxyoxetanyl ketones - Sahoo, Shubhranshu Shekhar; Kataria, Priyanka; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
The furan moiety, prevalent in bioactive natural products and essential drugs, presents intriguing structural features that have spurred our exploration into streamlined chemical synthesis routes for related natural products. In this study, we demonstrate the concise total synthesis of eight 2,4-disubstituted furan-derived natural products (including methylfuroic acid, rabdoketones A and B, paleofurans A and B, tournefolin C, and shikonofurans A and B). Our methodology revolves around the utilization of hydroxyoxetanyl ketones as pivotal intermediates. The approach encompasses transformations such as selective organo-catalyzed cross-ketol addition, synthesis of hydroxymethyl-tethered furans through Bi(OTf)3 catalyzed dehydrative cycloisomerization of alpha-hydroxyoxetanyl ketones, and a hydrogen atom transfer (HAT)-mediated oxidation of primary alcohols into the corresponding acids. This comprehensive synthetic strategy highlights the versatility of hydroxyoxetanyl ketones as invaluable building blocks in the synthesis of furan-containing natural products. A unified total synthesis of eight 2,4-disubstituted furan-derived natural products has been achieved through Bi(iii)-catalyzed cascade cycloisomerization of alpha-hydroxyoxetanyl ketones and hydrogen atom transfer-mediated oxidation of primary alcohols as pivotal transformations.